Blessed be the Children: A Case–Control Study of Sexual Abusers in the Catholic Church. (August 2015) - Calkins, Cynthia; Fargo, Jamison; Jeglic, Elizabeth; Terry, Karen
<x xml:space="preserve">Abstract</x> Individuals working in churches and other youth‐serving institutions have a unique level of access to children, yet the problem of sexual abuse in institutional settings has received scant research attention. To address this gap, we analyzed data from a large sample of clergy (N = 1, 121) and applied a social–ecological model of offending to identify risk factors for sexual abuse perpetration. Using a case–control study design that compared clergy sexual abusers with three control groups of clergy, this study focuses specifically on individual‐, relationship‐, and community‐level factors associated with a higher risk of abuse in professional populations. Findings revealed that clergy sexual abusers tended to have more truncated pre‐seminary dating histories, and that their dating and sexual partners were more likely to have been male than female. Self‐reported sexual abuse history was associated with a greater likelihood of sexual abuse perpetration among clergy. Clergy abusers tended to be more involved with youth and adolescents in their ministries; however, they were observed to relate less well to youth and adolescents than their clergy counterparts. Given widespread changes in our cultural understanding of abuse as well as more specific changes in the organizational approach to seminary education, these differences underscore the role that youth‐serving institutions and society can have in the primary prevention of child sexual abuse. Copyright © 2015 John Wiley & Sons, Ltd.